O papel do brincar na apropriação da linguagem escrita - Bomfim, Juliana Cristina (Editora Oficina Universitária, 2022)
In the work, play is strengthened as an object of study and as a guide for essential movements in vital processes for the constitution of intelligence and personality in childhood, setting up fundamental bases for learning written language in its vivacity. It is a textual composition that enhances necessary debates around the social role of the school dedicated to small children - particularly those of preschool age, from the places of their intellectual agents (staff, teachers and other professionals working in the school environment ) and the child in the educational environment. Within the discussions, scientific and political advances are established on the value of this school environment as a potentially organized space to foster necessary and favorable conditions for the human constitution - of adults and children - in its entirety and fullness. The content of the book thus invites us to revisit common sense certainties and ideas, considering current social, economic, political, and health issues and tensions and putting in perspective the ethical, political and social commitment of acting towards the formation of intelligences and harmonious personalities from the beginning of life. This educational process has a revolutionary and emancipatory character - even though we are aware of the opposing and alienating forces strengthened by a capitalist society like ours - because it is repeated every day to strengthen concrete and effective conditions for the full training of children and the professionals who educate them. .